The association between parental and adolescent substance misuse: findings from the Irish CASE study. (5th January 2015) - Keeley, Helen S.; Mongwa, T.; Corcoran, P.
Abstract : Background: Self-report data from 2716 adolescents aged 15–17 years old in Irish schools were analysed to consider the association between psycho-social factors and the presence of adolescent substance and alcohol abuse, with an emphasis on family circumstances. Methods: Data were collected using the 'Lifestyle and Coping Questionnaire' which includes questions about lifestyle, coping, problems, alcohol and drug use, deliberate self-harm, depression, anxiety, impulsivity and self-esteem. Two additional questions were added to the standard questionnaire regarding parental substance misuse. Results: Adolescent substance abuse was more common in boys; parental substance misuse increased the risk of adolescent abuse of alcohol and drugs; the increased risk was marginally higher if the parental substance abuse was maternal rather than paternal; the increased risk was higher if the parental substance abuse affected both rather than one of the parents, especially regarding adolescent drug abuse; the magnitude of the increased risk was similar for boys and girls. Parental substance misuse increased the risk of adolescent substance abuse even after adjusting for other family problems and the adolescent's psychological characteristics. Conclusions: This study indicates that parental substance misuse affects the development of both alcohol and drug misuse in adolescent children independent of other family problems and the psychological characteristics of the adolescent. A wider perspective is needed, including societal and family issues, especially parental behaviour, when attempting to reduce risk of adolescent addiction. The impact on children of parental substance misuse also needs consideration in clinical contexts.